Development of salt hydrate eutectics as latent heat storage for air conditioning and cooling - Efimova, Anastasia; Pinnau, Sebastian; Mischke, Matthias; Breitkopf, Cornelia; Ruck, Michael; Schmidt, Peer (Thermochimica Acta, 2014)
Sustainable air conditioning systems require heat reservoirs that operate between 4 and 20 C. A systematic search for binary and ternary eutectics of inorganic salts and salt hydrates with melting temperatures in this temperature regime and with high enthalpies of fusion has been performed by means of differential scanning calorimetry (DSC). Promising results were obtained for the pseudo-ternary system Zn(NO3)2·6H2O, Mn(NO3)2·4H2O, and KNO3 with the melting temperature range 18-21 C and the enthalpy of fusion of about 110 kJ kg-1. Suitable nucleating and thickening agents have been found and tested to prevent the mixture from supercooling and phase separation. © 2013 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cold storage; Latent heat thermal energy storage (LHTES); Phase change material (PCM); Salt hydrate eutectics